Folic Acid Is Able to Polarize the Inflammatory Response in LPS Activated Microglia by Regulating Multiple Signaling Pathways. (25th September 2016) - Cianciulli, Antonia; Salvatore, Rosaria; Porro, Chiara; Trotta, Teresa; Panaro, Maria Antonietta
Abstract : We investigated the ability of folic acid to modulate the inflammatory responses of LPS activated BV-2 microglia cells and the signal transduction pathways involved. To this aim, the BV-2 cell line was exposed to LPS as a proinflammatory response inducer, in presence or absence of various concentrations of folic acid. The production of nitric oxide (NO) was determined by the Griess test. The levels of tumor necrosis factor-alpha (TNF- α ), interleukin-1 beta (IL-1 β ), and IL-10 were determined by ELISA. Inducible NO synthase (iNOS), nuclear transcription factor-kappa B (NF- κ B) p65, MAPKs protein, and suppressors of cytokine signaling (SOCS)1 and SOCS3 were analyzed by western blotting. TNF- α and IL-1 β, as well as iNOS dependent NO production, resulted significantly inhibited by folic acid pretreatment in LPS-activated BV-2 cells. We also observed that folic acid dose-dependently upregulated both SOCS1 and SOCS3 expression in BV-2 cells, leading to an increased expression of the anti-inflammatory cytokine IL-10. Finally, p-I κ B α, which indirectly reflects NF- κ B complex activation, and JNK phosphorylation resulted dose-dependently downregulated by folic acid pretreatment of LPS-activated cells, whereas p38 MAPK phosphorylation resulted significantly upregulated by folic acid treatment. Overall, these results demonstrated that folic acid was able to modulate the inflammatory response in microglia cells, shifting proinflammatory versus anti-inflammatory responses through regulating multiple signaling pathways.